2019
DOI: 10.15632/jtam-pl/112456
|View full text |Cite
|
Sign up to set email alerts
|

Effects of X-ray on fibroblast mechanical properties

Abstract: Concerning the widespread use of X-rays to detect various diseases, such as oral and dental ones, it is essential to study the effects of this radiation on living cells. From the past, genetic effects and cell death because of X-rays have been studied. In addition, the effect of this ionizing radiation on the mechanical properties of the cell and cytoskeleton has been studied, but different results have been obtained based on different models. In this study, post-culture gingival fibroblast cells were classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Additionally, the gel point frequency was estimated to be about 23Hz in the study conducted by Azami et al on dermal broblast cells; this number is higher than that estimated for gingival cells. Nevertheless, the behavior of the cells at higher frequencies was comparable in both studies(Heydarian et al 2019b)(AmirhosseinAzami et al 2019).According to the results of the nite element analysis performed on these cells, the deformation of the cells occurs more often at their gel point frequency than at the operating frequency of the electric toothbrushes.Deformation of additional cells can result in an increase in cell mechanosensory, thereby enhancing tissue strength(Sarasa-Renedo and Chiquet 2005) (Wang et al 2007)(Chiquet et al 2003). In their investigation, Fernando et al demonstrated that stresses could change the function of cellular actin bers, resulting in the maintenance of the cytoskeleton and cellular scaffold regeneration(Valencia et al 2021).…”
mentioning
confidence: 73%
“…Additionally, the gel point frequency was estimated to be about 23Hz in the study conducted by Azami et al on dermal broblast cells; this number is higher than that estimated for gingival cells. Nevertheless, the behavior of the cells at higher frequencies was comparable in both studies(Heydarian et al 2019b)(AmirhosseinAzami et al 2019).According to the results of the nite element analysis performed on these cells, the deformation of the cells occurs more often at their gel point frequency than at the operating frequency of the electric toothbrushes.Deformation of additional cells can result in an increase in cell mechanosensory, thereby enhancing tissue strength(Sarasa-Renedo and Chiquet 2005) (Wang et al 2007)(Chiquet et al 2003). In their investigation, Fernando et al demonstrated that stresses could change the function of cellular actin bers, resulting in the maintenance of the cytoskeleton and cellular scaffold regeneration(Valencia et al 2021).…”
mentioning
confidence: 73%